Variations In The Use Of Affixes In Narrative Texts By BIPA Learners - Narlianti, Ni Putu Veny (International Journal of Linguistics and Discourse Analytics, 2024)
In the context of BIPA learning, understanding the variations in the use of affixes in narrative texts has great relevance. Narrative is a type of text that is often used in language learning to develop speaking, writing and reading comprehension skills. The use of affixes in narrative texts by BIPA students can be a reflection of their understanding of Indonesian and their ability to apply them in certain contexts. This research uses Indonesian grammar theory. Grammatical theory is used to examine grammatical variations in sentences used and errors in the use of affixes in sentences used by BIPA students. In the data collection stage, the observation method was used. In applying the listening method, it is then followed by the note-taking technique. The collected data was analyzed using the agih method with basic techniques, namely deletion, substitution and permutation, while formal and informal methods were used to present the analysis results. Based on research that has been conducted, the types of affixes taught to BIPA students are the prefixes ber-, meng-, peng-, per-, di-, ter-, ber- R. Confixes peng-…-an, per-...-an, ke-...-an, ber-…-an, se-…-nya, ber-R-an, se-R-nya.. The suffix -nya, -an, and the simulfix meng-...-kan, meng-...-i, memper-...-i, memper-...-kan, ber-...-kan. Of the affixes taught, the types of affixes that BIPA students are able to use are the prefixes meng-, ter-, di-, ber-, peng-, ber-R. Confix peng-...-an, ke-…-an, per-…-an, ber-…-an, se-...-nya. Suffix -an, -nya, and the simulfixes meng-...-kan, meng-...-i, memper-...-kan, and memper-...-i. Infixes are not used by BIPA students because they are not taught